Análise de dados de manutenção para avaliação da disponibilidade de equipamentos de ressonância magnética em estabelecimentos assistenciais de saúde - Alves, João Claudio Ferreira Soares (2019)
Magnetic Resonance Imaging (MRI) or only Magnetic Resonance (MR) is one of the most important imaging diagnostic and biomedical equipment on the market. However, this equipment is subject to unwanted downtime, affecting the availability of the device and, consequently, causing a reduction in the number of examinations performed by Health Care Establishments (HCEs), in addition to the high operating costs that are spent. The objective of this work was to conduct a study on the main factors affecting the availability and operating costs of magnetic resonance imaging equipment in public and private EASs, and through these values to verify their viability. The method initially adopted was the search for data in the field, that is, to obtain the pertinent data to the historical of occurrences of five different MR equipment. In addition, we tried to analyze the data related to the historical of costs, being, income and expenses for an EAS RM equipment. A priori from the history of occurrences it can be seen that there are categories of service interruptions that actually affect the availability of MRI equipment and, consequently, the amount of examinations performed, leading to economic losses by EASs. In addition, it can be seen that for the analyzed EAS the equipment expense amounts were operating at more than four times the revenue received by the EAS. The data show that there are categories of service interruption that affect the availability of MRI equipment, being detrimental to the safes of the EASs. Moreover, through the data it can be seen that for the analyzed EAS the provision of the MRI service is not feasible.